2024
DOI: 10.1038/s41598-023-50123-2
|View full text |Cite
|
Sign up to set email alerts
|

Rural Indonesian adolescents’ smoking behaviours during the COVID-19 pandemic: rapid survey and cotinine test of school-attend adolescents in Gunung Kidul, Yogyakarta

Fitriana Murriya Ekawati,
Dhiana Ayu Novitasari,
Dwi Astuti Dharma Putri
et al.

Abstract: The COVID-19 pandemic is predicted to affect adolescent smoking behaviours. We aim to map profiles of adolescents’ smoking behaviours in a rural district in Indonesia during the COVID-19 pandemic and validate their smoking exposures using cotinine tests. This study applied an online survey followed by cotinine tests for high-school students in Gunung Kidul, Yogyakarta. The participants were asked to complete the survey and participate in a cotinine test. Univariate and multivariate regressions were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The smoking prevalence has continued to increase in adolescents over the world but more to urban area and limited studies on the rural area. A study done in the rural area at Yogyakarta Indonesia, revealed the prevalence rate of adolescents smoking were 22.8% (Ekawati et al, 2024). The prevalence rate is nearly similar with the current study as this was the first study that has been conducted in a school located in the FELDA settlement area of Bandar Tun Abdul Razak, Pahang, Malaysia, in a rural area.…”
Section: Discussionsupporting
confidence: 86%
“…The smoking prevalence has continued to increase in adolescents over the world but more to urban area and limited studies on the rural area. A study done in the rural area at Yogyakarta Indonesia, revealed the prevalence rate of adolescents smoking were 22.8% (Ekawati et al, 2024). The prevalence rate is nearly similar with the current study as this was the first study that has been conducted in a school located in the FELDA settlement area of Bandar Tun Abdul Razak, Pahang, Malaysia, in a rural area.…”
Section: Discussionsupporting
confidence: 86%